Progesterone – Effective for Tocolysis and Maintenance Treatment After Arrested Preterm Labour? - Rath, Werner; Kuon, Ruben-J. (Geburtshilfe und Frauenheilkunde, 2019)
Numerous experimental studies indicate that natural progesterone, through various mechanisms, exerts an inhibitory effect on uterine contractility and sensitises the myometrium for tocolytics. It was therefore appropriate to investigate the possible benefits of oral/vaginal progesterone and the synthetic progesterone derivative 17-α-hydroxyprogesterone caproate, applied intramuscularly, in clinical studies on primary tocolysis, additively to established tocolytics (“adjunctive tocolysis”) and as maintenance treatment after successful tocolysis in cases of threatened preterm birth. Three studies with a small number of cases do not yield any sufficient evidence for recommending progesterone/17-α-hydroxyprogesterone caproate as primary tocolysis in women with preterm labour. There is also no evidence that progesterone or 17-α-hydroxyprogesterone caproate combined with commonly used tocolytics leads to a prolongation of pregnancy and a significant decrease in the rate of preterm birth. The data on the use of progesterone as maintenance treatment is controversial. While randomised, controlled studies with low quality showed promising results, studies with high quality did not reveal any significant differences with regard to the rate of preterm birth < 37 weeks of gestation, the latency period until delivery and in the neonatal outcome between progesterone/17-α-hydroxyprogesterone caproate and placebo or no treatment. Significant differences in the methodology, the inclusion and outcome criteria, the mode of application and the dosages of the substances as well as the inadequate statistical power as a result of low numbers of cases make interpretation and comparability of the studies difficult. Therefore, well-designed randomised, placebo-controlled, double-blind studies with uniform primary outcome criteria are needed in order to clarify whether progesterone and via which route of administration and at which dosage is of clinical benefit for patients with manifest preterm contractions and as maintenance treatment after arrested preterm labour.Zahlreiche experimentelle Studien weisen darauf hin, dass natürliches Progesteron über verschiedene Mechanismen einen inhibitorischen Effekt auf die uterine Kontraktilität ausübt und das Myometrium für Tokolytika sensibilisiert. Daher war es sinnvoll, die möglichen Vorteile von oralem/vaginalem Progesteron und des intramuskulär applizierten synthetischen Progesteronderivats 17-α-Hydroxyprogesteroncaproat in klinischen Studien zur primären Tokolyse, additiv zu etablierten Tokolytika („adjunktive Tokolyse“) und zur Erhaltungstherapie nach erfolgreicher Wehenhemmung bei drohender Frühgeburt zu untersuchen. Aus drei Studien mit kleiner Fallzahl ergibt sich keine ausreichende Evidenz, Progesteron/17-α-Hydroxyprogesteroncaproat zur primären Tokolyse bei Frauen mit vorzeitiger Wehentätigkeit zu empfehlen. Es gibt ebenfalls keine Evidenz dafür, dass Progesteron oder 17-α-Hydroxyprogesteroncaproat in Kombination mit gebräuchlichen Tokolytika zu einer Verlängerung der Schwangerschaft und zu einer signifikanten Senkung der Rate an Frühgeburten führt. Die Datenlage zur Anwendung von Progesteron zur Erhaltungstherapie ist kontrovers. Während randomisierte, kontrollierte Studien mit niedriger Qualität vielversprechende Ergebnisse zeigten, ergaben sich aus Studien mit hoher Qualität keine signifikanten Unterschiede hinsichtlich der Frühgeburtenrate < 37 SSW, der Latenzzeit bis zur Geburt und im neonatalen Outcome zwischen Progesteron/17-α-Hydroxyprogesteroncaproat und Placebo oder keiner Behandlung. Erhebliche Unterschiede in der Methodologie, den Einschluss- und Zielkriterien, dem Applikationsmodus und den Dosierungen der Substanzen sowie die inadäquate statistische Power infolge niedriger Fallzahlen macht eine Interpretation und Vergleichbarkeit der Studien schwierig. Daher sind gut konzipierte, randomisierte, placebokontrollierte Doppelblindstudien mit einheitlichen primären Zielkriterien notwendig, um zu klären, ob Progesteron und auf welchem Applikationsweg und mit welcher Dosierung bei Patientinnen mit manifesten vorzeitigen Wehen und zur Erhaltungstherapie nach initialer Wehenhemmung von klinischem Nutzen ist.
Keywords: preterm labour; progesterone; 17-α-hydroxyprogesterone caproate; tocolysis; maintenance treatment/tocolysis